Method for improving continuous crystal strength of iron ore powder

By equipped with finely grinding composite reinforcement in iron ore powder and improved the roasting temperature, the problem of insufficient strength of the chain-rotating kiln crafts in the rotary kiln craftsmanship has been solved, and the significant improvement of the intensity of the lingering crystal of the group ore is achieved.

CN119372451APending Publication Date: 2025-01-28SHANXI TAIGANG STAINLESS STEEL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411432868.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

In the chain grinder-rotary kiln process, the pellet ore produced by fine-grained iron ore powder is relatively low in strength, which is difficult to meet the needs of blast furnace smelting.

Method used

By equipped with finely grinding composite enhanced articles in iron ore powder, including Tshan Iron ore powder, iron scales and scorched powder, and appropriately increase the roasting temperature, through the ingredients, blocks, roasting and cooling processes, the team is made to make the team. mine.

Benefits of technology

A significant improvement of the connected crystal intensity of the group ore, the intensity range of the lian crystal is 2090-2430N, which exceeds the connected intensity of the traditional process.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

A method for improving pellet strength in pellet production with a chain grate-rotary kiln as a production process and fine-fraction iron ore powder as an iron material is characterized in that a mixture of finely ground magnetite powder, iron scale, coke powder and the like in a certain proportion is added into the iron ore powder, the roasting temperature is properly increased, the crystal connection capacity of the iron ore powder is improved, and the pellet strength is improved. And then preparing materials, agglomerating, roasting and cooling to obtain finished briquettes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of iron material pellets for blast furnace ironmaking, and in particular to a method for improving the continuous crystal strength of iron ore powder. Background Art

[0002] When using chain grate-rotary kiln as production process and fine-grained iron ore powder as iron material to produce pellets, improving the ability of iron ore powder to connect crystals can improve the physical performance indicators of pellets such as strength and particle size, which is beneficial to blast furnace smelting. Therefore, it is necessary to take measures to improve the strength of pellets.

[0003] The purpose of the present invention is to improve the continuous crystal strength of iron ore powder. Summary of the invention

[0004] The purpose of the present invention is to provide a method for improving the continuous crystal strength of iron ore powder in view of the above problems.

[0005] The object of the present invention is achieved as follows: A method for improving the continuous crystal strength of iron ore powder, comprising the following steps: Step 1: Preparation of composite reinforcement: When producing pellets, the raw materials and weight percentages of the composite reinforcement are: Jianshan iron ore powder: 70 parts, iron scale powder: 25 parts, coke powder: 5 parts, the above raw materials are mixed and ground in a ball mill to obtain a composite reinforcement, and the proportion of the composite reinforcement less than 0.044 mm is more than 70%; Step 2: Batching: The composite reinforcement, iron ore powder, and bentonite are weighed and batched according to the following weight percentages to obtain a mixture: composite reinforcement: 60-120 parts, iron ore powder: 870-93 0 parts, bentonite: 10 parts; Step 3: Mixing and block making: Mix the mixture with a mixer, add water, and use a sample making machine to make 10±2mm×10±2mm samples, namely test samples, with a moisture content of 7-9% by weight; Step 4: Roasting: Roast the samples in a high-temperature roasting furnace to obtain pellets, the preheating temperature is 800-900℃, the preheating time is 2-2.5min, the roasting temperature is 1180-1250℃, and the roasting time is 6-8min; Step 5: Cooling: The pellets are naturally cooled to obtain finished pellets, and the continuous crystal strength of the finished pellets is 2090-2430N.

[0006] The Jianshan iron ore powder in step one is magnetite powder, and its chemical composition is: TFe: 66.5~67.5, and the rest are impurities. The iron scale powder is the oxidized recovery product formed in the steel rolling process, and its chemical composition is: TFe: 72.8~75.2%, FeO: 65.2~65.5%, and the rest are impurities. The coke powder is the screened material in the coke production process, and its chemical composition is: fixed C is greater than 85%, and the rest are impurities.

[0007] In step 2, the content of iron ore powder with a particle size less than 0.044 mm is greater than 90%, the iron grade of the iron ore powder is greater than 63%, the FeO content is greater than 12%, and the SiO 2 The content is less than 6% and the moisture is less than 11%.

[0008] The beneficial effects of the present invention are as follows: in order to solve the problem of improving the continuous crystal strength of iron ore powder when producing pellets using a chain grate machine-rotary kiln as a production process and fine-grained iron ore powder as an iron material, a certain proportion of a mixture of finely ground magnetite powder, iron scale, coke powder, etc. is added to the iron ore powder, the roasting temperature is appropriately increased, the continuous crystal capacity of the iron ore powder is improved, and then the finished pellets are obtained through batching, agglomeration, roasting and cooling, thereby improving the strength of the pellets. DETAILED DESCRIPTION

[0009] In order to solve the problem of improving the strength of pellets when using chain grate machine-rotary kiln as the production process and fine-grained iron ore powder as the iron material to produce pellets, the present invention provides a method for improving the ability of iron ore powder to form continuous crystals. The specific steps of the present invention are as follows: (1) Preparation of composite reinforcement: When producing pellets, the composite reinforcement is weighed and mixed according to the following weight percentages, and the specific ratio is: Jianshan iron ore powder: 70, iron scale: 25, coke powder: 5.

[0010] Among them, Jianshan iron ore powder is magnetite powder produced by TISCO, with the main chemical composition of TFe 66.5~67.5. Iron scale powder (also called iron oxide) is the oxidized recycled product formed in the steel rolling process, with the main chemical composition of TFe 72.8~75.2% and FeO 65.2~65.5%. Coke powder is the screened material in the process of producing coke, with the main chemical composition of fixed C greater than 85%.

[0011] The above raw materials are mixed and ground in a ball mill to obtain a composite reinforcement (hereinafter collectively referred to as "composite reinforcement"), wherein the proportion of particles smaller than 0.044 mm is more than 70%.

[0012] (2) Ingredients: The composite reinforcement, iron ore powder and bentonite are weighed and mixed according to the following weight percentages. The specific ratio is: composite reinforcement: 60-120 parts, iron ore powder: 870-930 parts, bentonite: 10 parts (based on the total weight of the ingredients: 1000 parts).

[0013] The iron ore powder is from Lanxian County, Shanxi Province, with a particle size of less than 0.044 mm and a content of 99.5%. The iron grade of the iron ore powder is 65.8%, the FeO content is 15.3%, and the SiO 2 The content is 4.2%, CaO content is 0.48%, and moisture content is 10.7%.

[0014] (3) Mixing and block making: The above mixture is mixed by a mixer, and water is added. The mixture is then made into 10 mm × 10 mm blocks using a sample making machine, and the moisture content is 7% (by weight percentage).

[0015] (4) Calcination: Calcination in a high-temperature calcining furnace to obtain finished pellets; wherein the preheating temperature is 800-900°C, the preheating time is 2-2.5 minutes, the calcining temperature is 1180-1250°C, and the finished pellets are obtained by natural cooling.

[0016] (5) Cooling: After the above-mentioned roasted ore pellets are naturally air-cooled, the continuous crystal strength is 2090-2430N. Benchmark Example

[0017] The specific production steps of conventional fine-grained sintered ore are as follows: (1) Ingredients: Iron ore powder and lime are weighed and mixed according to the following weight percentages. The specific ratio is: iron ore powder: 990 parts, bentonite: 10 parts.

[0018] The iron ore powder is from Lanxian County, Shanxi Province, with a particle size of less than 0.044 mm and a content of 99.5%. The iron grade of the iron ore powder is 65.8%, the FeO content is 15.3%, and the SiO 2 The content is 4.2%, the CaO content is 0.48%, and the moisture content is 10.7%; the bentonite is conventional bentonite purchased on the market, and the proportion of particles less than 0.074mm is 86%.

[0019] (2) Mixing and block making: The above mixture is mixed by a mixer, and water is added. The mixture is then made into 10 mm × 10 mm blocks using a sample making machine, and the moisture content is 7% (by weight percentage).

[0020] (3) Calcination: Calcination in a high-temperature calcining furnace to obtain finished pellets; wherein the preheating temperature is 850°C, the preheating time is 2-2.5 minutes, the calcining temperature is 1180°C, the calcining time is 6 minutes, and the finished pellets are obtained.

[0021] (4) Cooling: After the above-mentioned roasted ore pellets are naturally air-cooled, the continuous crystal strength is 2010N.

[0022] The above benchmark example shows that the pellets produced by conventional technology have a low continuous crystal strength of 2010N.

[0023] The specific embodiments of the present invention are further described below by way of examples, but the specific embodiments of the present invention are not limited to the following examples. Example 1

[0024] This embodiment mainly adopts the method of adding a certain proportion of finely ground composite reinforcement to iron ore powder, and then obtaining finished pellets through batching, agglomeration, roasting and cooling. The specific steps and characteristics of this embodiment are as follows: (1) Preparation of composite reinforcement: When producing pellets, the composite reinforcement is weighed and batched according to the following weight percentages, and the specific ratio is: Jianshan iron ore powder: 70, iron scale: 25, coke powder: 5.

[0025] Among them, Jianshan iron ore powder is magnetite powder produced by TISCO, with the main chemical composition of TFe 66.5~67.5. Iron scale powder Iron scale (also called iron oxide) is an oxidized recycled product formed during steel rolling, with the main chemical composition of TFe 72.8~75.2% and FeO 65.2~65.5%. Coke powder is the screened material in the process of producing coke, with the main chemical composition of fixed C greater than 85%.

[0026] The above raw materials are mixed and ground in a ball mill to obtain a composite reinforcement (hereinafter collectively referred to as "composite reinforcement"), wherein the proportion of particles smaller than 0.044 mm is more than 70%.

[0027] (2) Ingredients: The composite reinforcement, iron ore powder and lime are weighed and mixed according to the following weight percentages. The specific ratio is: composite reinforcement: 60 parts, iron ore powder: 930 parts, bentonite: 10 parts.

[0028] The iron ore powder is from Lanxian County, Shanxi Province, with a particle size of less than 0.044 mm and a content of 99.5%. The iron grade of the iron ore powder is 65.8%, the FeO content is 15.3%, and the SiO 2 The content is 4.2%, the CaO content is 0.48%, and the moisture content is 10.7%; the bentonite is conventional bentonite purchased on the market, and the proportion of particles less than 0.074mm is 86%.

[0029] (3) Mixing and block making: The above mixture is mixed by a mixer, and water is added. The mixture is then made into 10 mm × 10 mm blocks using a sample making machine, and the moisture content is 7% (by weight percentage).

[0030] (4) Calcination: Calcination in a high temperature calcination furnace to obtain finished briquette ore; wherein the preheating temperature is 850°C, the preheating time is 2-2.5 min, the calcination temperature is 1180°C, the calcination time is 6 min, and the finished briquette ore is obtained.

[0031] (5) Cooling: After the above-mentioned roasted ore pellets are naturally air-cooled, the continuous crystal strength is 2090N. Example 2

[0032] This embodiment mainly adopts the method of adding a certain proportion of finely ground composite reinforcement to iron ore powder, and then obtaining finished pellets through batching, agglomeration, roasting and cooling. Compared with Example 1, the "composite reinforcement" used in this embodiment is increased from 60 parts to 80 parts, and the roasting temperature is increased from 1180°C to 1200°C.

[0033] The specific steps and features of this embodiment are as follows: (1) Preparation of composite reinforcement: When producing pellets, the composite reinforcement is weighed and mixed according to the following weight percentages, and the specific ratio is: Jianshan iron ore powder: 70, iron scale: 25, coke powder: 5.

[0034] Among them, Jianshan iron ore powder is magnetite powder produced by TISCO, with the main chemical composition of TFe 66.5~67.5. Iron scale powder Iron scale (also called iron oxide) is an oxidized recycled product formed during steel rolling, with the main chemical composition of TFe 72.8~75.2% and FeO 65.2~65.5%. Coke powder is the screened material in the process of producing coke, with the main chemical composition of fixed C greater than 85%.

[0035] The above raw materials are mixed and ground in a ball mill to obtain a composite reinforcement (hereinafter collectively referred to as "composite reinforcement"), wherein the proportion of particles smaller than 0.044 mm is more than 70%.

[0036] (2) Ingredients: The composite reinforcement, iron ore powder and lime are weighed and mixed according to the following weight percentages. The specific ratio is: composite reinforcement: 80 parts, iron ore powder: 910 parts, bentonite: 10 parts.

[0037] The iron ore powder is from Lanxian County, Shanxi Province, with a particle size of less than 0.044 mm and a content of 99.5%. The iron grade of the iron ore powder is 65.8%, the FeO content is 15.3%, and the SiO 2 The content is 4.2%, the CaO content is 0.48%, and the moisture content is 10.7%; the bentonite is conventional bentonite purchased on the market, and the proportion of particles less than 0.074mm is 86%.

[0038] (3) Mixing and block making: The above mixture is mixed by a mixer, and water is added. The mixture is then made into 10 mm × 10 mm blocks using a sample making machine, and the moisture content is 7% (by weight percentage).

[0039] (4) Calcination: Calcination in a high-temperature calcination furnace to obtain finished briquette ore; wherein the preheating temperature is 850°C, the preheating time is 2-2.5 minutes, the calcination temperature is 1200°C, the calcination time is 6 minutes, and the finished briquette ore is obtained.

[0040] (5) Cooling: After the above-mentioned roasted ore pellets are naturally air-cooled, the continuous crystal strength is 2250N. Example 3

[0041] This embodiment mainly adopts the method of adding a certain proportion of finely ground composite reinforcement to iron ore powder, and then obtaining finished briquette ore through batching, agglomeration, roasting and cooling. Compared with Example 2, the "composite reinforcement" used in this embodiment is increased from 80 parts to 100 parts, and the roasting temperature is increased from 1200°C to 1230°C.

[0042] The specific steps and features of this embodiment are as follows: (1) Preparation of composite reinforcement: When producing briquette, the composite reinforcement is weighed and mixed according to the following weight percentages, and the specific ratio is: Jianshan iron ore powder: 70, iron scale: 25, coke powder: 5.

[0043] Among them, Jianshan iron ore powder is magnetite powder produced by TISCO, with the main chemical composition of TFe 66.5~67.5. Iron scale powder Iron scale (also called iron oxide) is an oxidized recycled product formed during steel rolling, with the main chemical composition of TFe 72.8~75.2% and FeO 65.2~65.5%. Coke powder is the screened material in the process of producing coke, with the main chemical composition of fixed C greater than 85%.

[0044] The above raw materials are mixed and ground in a ball mill to obtain a composite reinforcement (hereinafter collectively referred to as "composite reinforcement"), wherein the proportion of particles smaller than 0.044 mm is more than 70%.

[0045] (2) Ingredients: The composite reinforcement, iron ore powder and lime are weighed and mixed according to the following weight percentages. The specific ratio is: composite reinforcement: 100 parts, iron ore powder: 890 parts, bentonite: 10 parts.

[0046] The iron ore powder is from Lanxian County, Shanxi Province, with a particle size of less than 0.044 mm and a content of 99.5%. The iron grade of the iron ore powder is 65.8%, the FeO content is 15.3%, and the SiO 2 The content is 4.2%, the CaO content is 0.48%, and the moisture content is 10.7%; the bentonite is conventional bentonite purchased on the market, and the proportion of particles less than 0.074mm is 86%.

[0047] (3) Mixing and pelletizing: The above mixture is mixed by a mixer, water is added, and a 10 mm × 10 mm sample block is formed by a sample making machine, with a moisture content of 7% (by weight percentage).

[0048] (4) Calcination: Calcination in a high temperature calcination furnace to obtain finished briquette ore; wherein the preheating temperature is 850°C, the preheating time is 2-2.5 min, the calcination temperature is 1230°C, the calcination time is 6 min, and the finished briquette ore is obtained.

[0049] (5) Cooling: After the above-mentioned roasted ore pellets are naturally air-cooled, the continuous crystal strength is 2390N. Example 4

[0050] This embodiment mainly adopts the method of adding a certain proportion of finely ground composite reinforcement to iron ore powder, and then obtaining finished briquette ore through batching, agglomeration, roasting and cooling. Compared with Example 3, the "composite reinforcement" used in this embodiment is increased from 100 parts to 120 parts, and the roasting temperature is increased from 1230°C.

[0051] The specific steps and features of this embodiment are as follows: (1) Preparation of composite reinforcement: When producing pellets, the composite reinforcement is weighed and mixed according to the following weight percentages, and the specific ratio is: Jianshan iron ore powder: 70, iron scale: 25, coke powder: 5.

[0052] Among them, Jianshan iron ore powder is magnetite powder produced by TISCO, with the main chemical composition of TFe 66.5~67.5. Iron scale powder Iron scale (also called iron oxide) is an oxidized recycled product formed during steel rolling, with the main chemical composition of TFe 72.8~75.2% and FeO 65.2~65.5%. Coke powder is the screened material in the process of producing coke, with the main chemical composition of fixed C greater than 85%.

[0053] The above raw materials are mixed and ground in a ball mill to obtain a composite reinforcement (hereinafter collectively referred to as "composite reinforcement"), wherein the proportion of particles smaller than 0.044 mm is more than 70%.

[0054] (2) Ingredients: The composite reinforcement, iron ore powder and lime are weighed and mixed according to the following weight percentages. The specific ratio is: composite reinforcement: 120 parts, iron ore powder: 870 parts, bentonite: 10 parts.

[0055] The iron ore powder is from Lanxian County, Shanxi Province, with a particle size of less than 0.044 mm and a content of 99.5%. The iron grade of the iron ore powder is 65.8%, the FeO content is 15.3%, and the SiO 2 The content is 4.2%, the CaO content is 0.48%, and the moisture content is 10.7%; the bentonite is conventional bentonite purchased on the market, and the proportion of particles less than 0.074mm is 86%.

[0056] (3) Mixing and block making: The above mixture is mixed by a mixer, and water is added. The mixture is then made into 10 mm × 10 mm blocks using a sample making machine, and the moisture content is 7% (by weight percentage).

[0057] (4) Calcination: Calcination in a high-temperature calcination furnace to obtain finished briquette ore; wherein the preheating temperature is 850°C, the preheating time is 2-2.5 minutes, the calcination temperature is 1250°C, the calcination time is 6 minutes, and the finished briquette ore is obtained.

[0058] (5) Cooling: After the above-mentioned roasted ore pellets are naturally air-cooled, the continuous crystal strength is 2410N. Example 5

[0059] This embodiment mainly adopts the method of adding a certain proportion of finely ground composite reinforcement to iron ore powder, and then obtaining finished briquette ore through batching, agglomeration, roasting and cooling. Compared with Example 3, the "composite reinforcement" used in this embodiment is increased from 100 parts to 120 parts, and the roasting temperature is increased from 1230°C to 1250°C.

[0060] The specific steps and features of this embodiment are as follows: (1) Preparation of composite reinforcement: When producing pellets, the composite reinforcement is weighed and mixed according to the following weight percentages, and the specific ratio is: Jianshan iron ore powder: 70, iron scale: 25, coke powder: 5.

[0061] Among them, Jianshan iron ore powder is magnetite powder produced by TISCO, with the main chemical composition of TFe 66.5~67.5. Iron scale powder Iron scale (also called iron oxide) is an oxidized recycled product formed during steel rolling, with the main chemical composition of TFe 72.8~75.2% and FeO 65.2~65.5%. Coke powder is the screened material in the process of producing coke, with the main chemical composition of fixed C greater than 85%.

[0062] The above raw materials are mixed and ground in a ball mill to obtain a composite reinforcement (hereinafter collectively referred to as "composite reinforcement"), wherein the proportion of particles smaller than 0.044 mm is more than 70%.

[0063] (2) Ingredients: The composite reinforcement, iron ore powder and lime are weighed and mixed according to the following weight percentages. The specific ratio is: composite reinforcement: 120 parts, iron ore powder: 870 parts, bentonite: 10 parts.

[0064] The iron ore powder is from Lanxian County, Shanxi Province, with a particle size of less than 0.044 mm and a content of 99.5%. The iron grade of the iron ore powder is 65.8%, the FeO content is 15.3%, and the SiO 2 The content is 4.2%, the CaO content is 0.48%, and the moisture content is 10.7%; the bentonite is conventional bentonite purchased on the market, and the proportion of particles less than 0.074mm is 86%.

[0065] (3) Mixing and block making: The above mixture is mixed by a mixer, and water is added. The mixture is then made into 10 mm × 10 mm blocks using a sample making machine, and the moisture content is 7% (by weight percentage).

[0066] (4) Calcination: Calcination in a high-temperature calcination furnace to obtain finished briquette ore; wherein the preheating temperature is 850°C, the preheating time is 2-2.5 minutes, the calcination temperature is 1250°C, the calcination time is 6 minutes, and the finished briquette ore is obtained.

[0067] (5) Cooling: After the above-mentioned roasted ore pellets are naturally air-cooled, the continuous crystal strength is 2430N.

[0068] The above embodiments are compared with the benchmark embodiment: For Example 1 of the present invention, 60 parts of finely ground composite reinforcement are added to the iron ore powder, and then after batching, agglomeration, roasting and cooling, the finished agglomerate is obtained, and the continuous crystal strength is 2090N, which is 60N higher than 2030N of the benchmark embodiment.

[0069] In Example 2 of the present invention, 80 parts of finely ground composite reinforcement are added to the iron ore powder, the roasting temperature is increased to 1200°C, and then the finished briquette is obtained through batching, agglomeration, roasting and cooling. The continuous crystal strength is 2250N, which is 120N higher than 2030N in the benchmark example.

[0070] In Example 3 of the present invention, 100 parts of finely ground composite reinforcement are added to the iron ore powder, the roasting temperature is increased to 1230°C, and then the finished briquette is obtained through batching, agglomeration, roasting and cooling. The continuous crystal strength is 2390N, which is 260N higher than 2030N in the benchmark example.

[0071] In Example 4 of the present invention, 120 parts of finely ground composite reinforcement were added to the iron ore powder, the roasting temperature was increased to 1230°C, and then the finished briquette was obtained through batching, agglomeration, roasting and cooling. The continuous crystal strength was 2410N, which was 280N higher than 2030N in the base example. The increase was not much compared with Example 3.

[0072] In Example 5 of the present invention, 120 parts of finely ground composite reinforcement were added to the iron ore powder, the roasting temperature was increased to 1250°C, and then the finished briquette was obtained through batching, agglomeration, roasting and cooling. The continuous crystal strength was 2430N, which was 300N higher than 2030N of the base example. The increase was not much compared with Example 3.

[0073] The above description is only a specific embodiment of the present invention, but the structural features of the protection scope of the present invention are not limited thereto. Any changes or modifications made by any technician in the field of the present invention are all covered by the patent scope of the present invention.

Claims

1. A method for improving the continuous crystal strength of iron ore powder, characterized in that: The following steps are involved: Step 1: Preparation of composite reinforcement: When producing pellets, the raw materials and weight percentages of the composite reinforcement are: Jianshan iron ore powder: 70 parts, iron scale powder: 25 parts, coke powder: 5 parts. The above raw materials are mixed and ground in a ball mill to obtain a composite reinforcement, and the proportion of the composite reinforcement less than 0.044 mm is more than 70%; Step 2: Ingredients: The composite reinforcement, iron ore powder, and bentonite are weighed and mixed according to the following weight percentages to obtain a mixture: composite reinforcement: 60-120 parts, iron ore powder: 870-930 parts, bentonite: 10 parts; Step 3: Mixing and block making: Mix the mixture with a mixer, add water, and use a sample making machine to make 10±2mm×10±2mm blocks, i.e. test samples, with a moisture content of 7-9% by weight; Step 4: Calcination: Calcinate the sample in a high temperature calciner to obtain pellets. The preheating temperature is 800-900°C, the preheating time is 2-2.5 minutes, the calcination temperature is 1180-1250°C, and the calcination time is 6-8 minutes. Step 5: Cooling: The pellets are naturally cooled to obtain finished pellets, and the continuous crystal strength of the finished pellets is 2090-2430N.

2. A method for improving the continuous crystal strength of iron ore powder according to claim 1, characterized in that: The Jianshan iron ore powder in step one is magnetite powder, and its chemical composition is: TFe: 66.5~67.5, and the rest are impurities. The iron scale powder is the oxidized recovery product formed in the steel rolling process, and its chemical composition is: TFe: 72.8~75.2%, FeO: 65.2~65.5%, and the rest are impurities. The coke powder is the screened material in the coke production process, and its chemical composition is: fixed C is greater than 85%, and the rest are impurities.

3. The method for improving the continuous crystal strength of iron ore powder according to claim 1, characterized in that: In step 2, the content of iron ore powder with a particle size less than 0.044 mm is greater than 90%, the iron grade of the iron ore powder is greater than 63%, the FeO content is greater than 12%, the SiO2 content is less than 6%, and the moisture content is less than 11%.